Occupational Noise Exposure and Risk for Noise-Induced Hearing Loss Due to Temporal Bone Drilling. Issue 6 (July 2018) - Vaisbuch, Yona; Alyono, Jennifer C.; Kandathil, Cherian; Wu, Stanley H.; Fitzgerald, Matthew B.; Jackler, Robert K.
Abstract : Background: Noise-induced hearing loss is one of the most common occupational hazards in the United States. Several studies have described noise-induced hearing loss in patients following mastoidectomy. Although otolaryngologists care for patients with noise-induced hearing loss, few studies in the English literature have examined surgeons' occupational risk. Methods: Noise dosimeters and sound level meters with octave band analyzers were used to assess noise exposure during drilling of temporal bones intraoperatively and in a lab setting. Frequency specific sound intensities were recorded. Sound produced using burrs of varying size and type were compared. Differences while drilling varying anatomic structures were assessed using drills from two manufacturers. Pure tone audiometry was performed on 7 to 10 otolaryngology residents before and after a temporal bone practicum to assess for threshold shifts. Results: Noise exposure during otologic drilling can exceed over 100 dB for short periods of time, and is especially loud using large diameter burrs > 4 mm, with cutting as compared with diamond burrs, and while drilling denser bone such as the cortex. Intensity peaks were found at 2.5, 5, and 6.3 kHz. Drilling on the tegmen and sigmoid sinus revealed peaks at 10 and 12.5 kHz. No temporary threshold shifts were found at 3 to 6 kHz, but were found at 8 to 16 kHz, though this did not reach statistical significance. Conclusion: This article examines noise exposure and threshold shifts during temporal bone drilling. We were unable to find previous descriptions in the literature of measurements done while multiple people drilling simultaneously, during tranlabyrinthine surgery and a specific frequency characterization of the change in peach that appears while drilling on the tegmen. Hearing protection should be considered, which would still allow the surgeon to appreciate pitch changes associated with drilling on sensitive structures and communication with surgical team members. As professionals who specialize in promoting the restoration and preservation of hearing for others, otologic surgeons should not neglect hearing protection for themselves.